Uma experiência do Programa Ensino Médio Inovador em Ananindeua – Pará - CASTRO, Maria Rosana de Oliveira (Universidade Federal do Pará, 2017)
“An experience of Innovator High School Program in Ananindeua—Pará” is a result of a doctor degree project which had the goal of analyze the process of the implementation of ProEMI at EEEFM Prof. Antônio Gondim Lins, in Ananindeua—Pará, from 2009 to 2015, mainly about the school management and the improvement in the students’ learning results. It was followed the methodological focus on the qualitative approach, through a case study, using as data achievement tool the literature review, document analyses and semi-structured interview. The text opens a discussion about the role of the State in front of the public-private partnerships in its process of regulation and implantation, and about the structural crises of the capital which ended up in the redefinition of the State’s role, which transferred the public services considered essential to the private sectors. It also debates the public and private concepts, highlighting the public-private partnerships in the Brazilian education in Brazil and Pará. It was realized a contextualization in the State of Pará, showing its social and cultural diversity , where it is focused the countryside violence, social inequality, the poverty and a educational system which deserves more attention and public investments, mainly in the basic education. The paper shows the national policy to the High School in Brazil, with information about this level of education and contextualized with the current educational legislation, approaching to experts who defends this level of education integrated with all life situations. It is also discussed the process of implementation of ProEMI at EEEFM prof. Antônio Gondim Lins revealing the unfamiliarity of the scholar community about this Program, showing that it was not discussed in this school and that SEDUC-PA did not accomplished its role in the guarantee of right conditions to implement ProEMI which, despite having destined resources to the school twice, it was used unduly.